From Aristotle to Eco: A Semio-Rhetorical Analysis of Corporate Financial Reporting and Meaning Management on the Indonesia Stock Exchange (2014–2024) - Apollo, Apollo (Dinasti International Journal of Management Science, 2026)
This study examines corporate financial reporting as a strategic management communication practice rather than merely a technical disclosure of financial data. Drawing on Aristotle’s classical rhetorical framework (ethos, logos, and pathos) and integrating semiotic theories developed by Ferdinand de Saussure, Charles Sanders Peirce, Roland Barthes, Roman Jakobson, Charles Morris, and Umberto Eco, this research applies a semio-rhetorical approach to analyze how meaning, legitimacy, and corporate identity are constructed in financial discourse. The study analyzes Annual Reports and Sustainability Reports of 21 publicly listed manufacturing companies on the Indonesia Stock Exchange (IDX) from 2014 to 2024. Using NVivo 14 Plus, the research conducts systematic narrative coding to identify rhetorical appeals and semiotic sign systems—including icon, index, and symbol—across textual, numerical, and visual disclosures. The findings indicate that corporate financial reporting functions as a form of managerial meaning management. Ethos is constructed through governance narratives, ethical positioning, and ESG disclosures; logos is reinforced through the selective structuring and visualization of financial data to establish numerical legitimacy; and mythos, following Barthes’ theory of myth, emerges in corporate narratives emphasizing resilience, innovation, and national contribution. Jakobson’s communicative functions and Morris’s pragmatic semiotics further demonstrate how financial language operates beyond information delivery to shape stakeholder interpretation, while Eco’s concept of the open text explains the interpretive flexibility of financial reports across different audiences. This study introduces the Financial Semio-Rhetorical Model (FSRM) as a conceptual contribution that synthesizes classical rhetoric and multi-layered semiotic theory to explain how financial reporting operates as a symbolic and strategic management tool. The findings contribute to management science by demonstrating that financial reports are not neutral representations, but discursive instruments through which organizations manage perception, legitimacy, and trust in emerging capital markets.